Proliferative leukoplakia: Proposed new clinical diagnostic criteria. (2nd May 2018) - Villa, A; Menon, RS; Kerr, AR; De Abreu Alves, F; Guollo, A; Ojeda, D; Woo, SB
Abstract : Objective: We aimed to characterize proliferative verrucous leukoplakia (PVL) from a clinical and histopathological standpoint and suggest an updated classification. Subjects and Methods: Records of patients seen at three oral medicine centers with a clinical diagnosis of PVL were reviewed for clinical and histopathological features and malignant transformation (MT). Results: There were 42 patients (median age: 69 years [range: 36–88]; 35 females). 12.2% were current smokers. Family history of cancer was present in 43.7% of patients. Partial demarcation of lesion margins was present in 31.3% of lesions, followed by verrucous (27.5%), smooth (22.7%) erythematous (22.3%), and fissured (18.3%) appearance. Large and contiguous and multisite and non‐contiguous lesions comprised 57.1% (24/42) and 35.7% (15/42) of PVL cases, respectively. 19.1% had prominent erythema (erythroleukoplakia). The most common histopathological diagnosis at first visit was hyperkeratosis without dysplasia (22/42; 56.4%). MT occurred in 71.4% patients after a median of 37 months [range: 1–210] from initial visit; erythroleukoplakia exhibited MT in 100% of cases. Conclusion: The generic term "proliferative leukoplakia (PL)" may be more appropriate than PVL because 18.3% were fissured and 22.7% erythematous. We also propose the term proliferative erythroleukoplakia to more accurately describe the subset of PL with prominent erythema, which had the highest MT rate.